2010
DOI: 10.1603/me10048
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Environmental Temperature and Humidity on Temporal Decomposition of Cockroach Allergens Bla g 1 and Bla g 2 in Feces

Abstract: The aim of the study was to establish a model of the environmental fate of German cockroach (Blattella germanica L.) allergens Bla g 1 and Bla g 2 in feces under controlled and field conditions. Temporal decline (3, 6, and 9 mo) of allergens Bla g 1 and Bla g 2 in the feces protected from cleaning was measured under laboratory and experimental household conditions. The influence of environmental temperature (15, 20, 25, 30, and 35 degrees C) and moisture (53, 75, 85, and 100% RH) on allergen degradation was es… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 32 publications
(27 reference statements)
0
4
0
1
Order By: Relevance
“…Allergen avoidance is the best method, theoretically, for preventing allergic disease and manifestation. However, Per a 2 and Bla g 2, the major group 2 German cockroach allergens, could exist for more than a year in the household environment [ 20 , 44 ]. It might be difficult for allergic patients to avoid these long-term cockroach allergens.…”
Section: Discussionmentioning
confidence: 99%
“…Allergen avoidance is the best method, theoretically, for preventing allergic disease and manifestation. However, Per a 2 and Bla g 2, the major group 2 German cockroach allergens, could exist for more than a year in the household environment [ 20 , 44 ]. It might be difficult for allergic patients to avoid these long-term cockroach allergens.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that Bla g 2, the major Group 2 German cockroach allergen, 37 can exist in an apartment with a half-life of 406 days at proper temperature and humidity. 38 Whether Per a 2 is as robust in the environment as Bla g 2 requires more studies.…”
Section: Discussionmentioning
confidence: 99%
“…The most important direct effect is associated with the contamination of www.videleaf.com food by arthropod fragments, which can be carcinogenic or allergenic. Stored-product pests, mites, and insects produce a variety of chemical compounds that cause allergic reactions in humans and domestic pets [15,16]. Indirectly, stored pests change the moisture content and temperature of stored food, developing optimal conditions for the growth of pathogenic microorganisms [17], or they host and transmit microorganisms, including antibiotic-resistant strains [18,19].…”
Section: Risks Associated With Storage Pestsmentioning
confidence: 99%